Analisis Peranan Motivasi Kerja Dalam Upaya Peningkatan Kinerja Pegawai Bidang Prasarana Pada Dinas Perhubungan Kota Bekasi - Putri, Marsesha Harywati; Utami, Renisya Ayu (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This study aims to analyze the role of work motivation in an effort to improve the performance of employees in the Infrastructure Sector at the Bekasi City Transportation Service. This research method is descriptive analysis with a qualitative approach. This research was carried out in the work environment of the Infrastructure Sector at the Bekasi City Transportation Service by selecting 7 (seven) informants who were considered to represent the entire population. Data collection techniques used in this study were direct field observations, interviews and documentation. The results showed that work motivation has an effect on efforts to improve the performance of employees in the Infrastructure Sector at the Bekasi City Transportation Service. The higher the work motivation given by the leadership, the higher the employee's performance will increase.